The Compliance of Hospital Nurse in the Prevention of Urinary Tract Infection in Surabaya, Indonesia - Ainun Azizah Ramdhani; Nur Annisha Karunia Latief; Fariani Syahrul; Dwiono Mudjianto (Universitas Airlangga, 2021)
Background: Catheter-Associated Urinary Tract Infection (CAUTI) is one of the most common infections in the hospital. In order to prevent and control CAUTI incidence, nurses are required to implement bundles of prevention. However, the lack of nurses’ compliance behavior in implementing the CAUTI bundle prevention was found. Objective: This study analyzes the nurse’s compliance behavior in implementing CAUTI prevention using the Theory of Planned Behavior (TPB) approach. Methods: This study was an analytical descriptive study with a cross-sectional design. Nurses who work in ICU, ICCU, HCU, and in-patient unit of the hospital were set as study population and taken as samples using simple random sampling. Background factors (age, education, knowledge, employment duration, career levels), attitudes, subjective norms, Perceived Behavior Control (PBC), and intention were determined as independent variables. In contrast, nurses’ compliance behavior in CAUTI prevention bundle implementation was determined as the dependent variable. Data were collected using a questionnaire and analyzed using logistic regression with a significance level of α < 0.05. Results: Among 111 nurses, most of them are in the age of 26-45 years (80.1%), has worked as a nurse for 8-13 years (29.7%), reach career level at Clinical Nurse 3 (51.4%), and have good knowledge about CAUTI prevention bundle (83.8%). The employment duration and career levels are background factors that correlate the most to the TPB factors. The nurses’ compliance behavior is influenced by attitude, subjective norm, PBC, and intention (P Value= 0.000). Multivariate analysis shows that intention is associated with nurses’ compliance behavior and increases nurses’ commitment to implement CAUTI prevention bundle (P Value= 0.033, OR= 6.46). Conclusion: The intention simultaneously influences the nurses’ compliance behavior.